The management of mass burn casualties and fire disasters : proceedings of the First international conference on burns and fire disasters - Gunn, S. William; Masellis, Michele (Kluwer Academic Publishers, 1992)
The health professionals are continually developing effective techniques of burns and mass casualty management. In parallel, fire prevention and fire-fighting techniques have developed considerably in most communities. It is therefore surprising that, while aiming at the same objective, the two sectors have rarely come together. The Mediterranean Burns Club is a professional organization that brings together persons concerned with burns therapy and with fire safety in all forms. Identified by the United Nations as a premier scientific body in its field within the programme of the International Decade for Natural Disaster Reduction, it initiated the first international gathering of specialists in burns as a surgical, clinical problem, and of counterparts dealing with fires as a social, disaster problem. This novel approach and symbiosis proved timely and succesful. This, the resulting book, reflects the commitment of all concerned to the reduction of fire disasters and the improvement of burns therapy.
Keywords: Rescue Work; management, organizace a řízení zdravotnictví; záchranná práce; Burn Units; katastrofy; Disasters; urgentní zdravotnické služby; popáleninové jednotky; Emergency Medical Services